Perspectives on hemorrhoids and their management among gastroenterologists across India: findings from in-clinic questionnaire-based survey studies - Khairnar, Harshad; Khobragade, Kunal J.; Borkar, Nilesh E. (International Journal Of Community Medicine And Public Health, 2025)
Background: Hemorrhoids are associated with bleeding, pain, itching, exudation and swelling with a high increasing prevalence, hence the current survey was designed to assess the real-world perspectives of demographic characteristics and practical approaches utilized by Gastroenterologists in managing hemorrhoids and bleeding hemorrhoids with a focus on Euphorbia prostrata (EP) and its combinations. Methods: Two real-world in-clinic observational surveys, which utilized digitally enabled questionnaires for data collection, were conducted between January and March 2023 and July and September 2023, involving 325 Gastroenterologists from various regions of India. Results: 40% of gastroenterologists managed 10 to 20 cases of bleeding hemorrhoids per month, while the patients suffering from various grades of hemorrhoids were Grade 1 (25%), Grade 2 (45%), Grade 3 (20%) & Grade 4 (10%), with bleeding (85%), pain (82%) as major sign and symptoms. In bleeding hemorrhoids, the thrombosed complication was higher, i.e., 59.75%, as compared to hemorrhoids patients. The notable role of EP was reduction in 67% bleeding, 57% pain with wound healing in 78% of patients. Further in bleeding hemorrhoids combination of flavonoids plus calcium dobesilate was most preferred (96.28%), which corelated to the usage of EP plus calcium dobesilate in clinical practice with its high effectiveness (73.07%) in bleeding hemorrhoids. Conclusions: Hemorrhoids are the most prevalent diagnosis among patients treated by Gastroentrologist. EP is the most commonly used drug for the treatment of hemorrhoids, while EP plus calcium dobesilate, being the preferred combination in management of bleeding hemorrhoids.